Content Diversity As A Predictor Of Digital Media Consumption By Generation Z: A Study On The Vidio Platform In Indonesia - Safrudiningsih Safrudiningsih; Sisca T. Gurning; Adlino Dananjaya; Dias Suminta (Journal of Research in Social Science and Humanities, 2025)
The transformation of digital media in the era of streaming platforms has influenced how Generation Z accesses entertainment and information. They are currently the users who dominate the preference for video-based services in digital media. This study aims to analyze the diversity of content on one of Indonesia's streaming platforms, Vidio, as a predictor of digital media consumption among Generation Z in Indonesia. The research method used a quantitative approach through the distribution of online questionnaires to 117 respondents representing regions in Indonesia. The research instrument used a five-point Likert scale, which was tested for validity using Pearson Correlation and reliability using Cronbach's Alpha through the SPSS program. Simple regression analysis was used to test the effect of content diversity on digital media consumption. The results of the study show that the diversity of Vidio content, which includes a variety of entertainment, sports, and local content, has a significant relationship with Gen Z's digital media consumption. These findings indicate that the intensity and frequency of users consuming digital media through the Vidio platform is increasing. This study confirms that content is a key factor in building user engagement and the competitiveness of local platforms amid the dominance of global streaming services. The implications of this study are recommendations to improve the quality of content curation and strategic differentiation development as efforts to strengthen Vidio's position in Indonesia.